Tindak Tutur Komisif Dalam Pementasan Ketoprak Lakon Rembulan Wungu: Analisis Sociopragmatik - Setyawan, Bagus Wahyu; Hidayah, Sa'adatun Nuril; Saddhono, Kundharu (SPHOTA: Jurnal Linguistik dan Sastra, 2023)
The branch of pragmatics makes speech acts as the main object of its study. Speech acts do not have to be spoken directly by the speaker but can take other forms such as in literary works. The purpose of this study is to describe and explain the form of commissive speech acts in the performance of the play Rembulan Wungu. This research is included in qualitative research using a pragmatic approach. The primary source of data in this study is the performance of the play Rembulan Wungu by Bondan Nusantara. Data retrieval techniques using listen, engage, and record techniques. The instrument used for data retrieval is a data card. The stages of data analysis consist of data classification, data condensation, data presentation and analysis, and drawing conclusions. The results of the study found three types of commissive speech acts in the performance of the play Rembulan Wungu, namely commissive speech acts intending, promising, and swearing. The most intent commissive speech acts were found with a total of 9 data with the most dominant verbal markers in the form of the words yen and ajeng. The commissive speech act promises 3 data with verbal markers in the form of the word bakal. An interesting thing is found in the type of oath that is pronounced using sesanti in the form of parikan or Javanese poem.